The effect of neuromuscular training on improving some skill performances in basketball - Al Kitani, Mahfoodha (Journal of Physical Education, 2024)
The aim of the recent study was to examine the effect of neuromuscular training on performance layup and free throw shots performance among female basketball students. Study sample was female students of physical education and sport sciences department (Age 20.21±39.0) who volunteered to participate in this study. Thirty-seven female students participated in this study, where (21) female students were selected to be experimental group of neuromuscular exercises. A sample of (16) female students was used for the exploratory study from the original community. Results showed that neuromuscular exercises can improve the chosen basketball skills (free-throw and layup-shot shooting). The contribution of neuromuscular training in a positive way to the free-throw and layup-shooting skills.